OP0008 Synovial Fibroblast Proliferation Is Enhanced by Microrna-223 Delivery through Monocyte-Derived Microparticles. (15th July 2016) - Meier, F.M.; Gilchrist, D.S.; McCarey, D.W.; McIntyre, D.; Melchor, E.G.; Morton, B.E.; Müller-Ladner, U.; McInnes, I.B.; Kurowska-Stolarska, M.
Abstract : Background: Microparticles (MPs) have been described to function as extracellular vehicles that shuttle microRNAs (miR) from platelets to endothelial cells 1 and regulate recipient cell gene expression. Crosstalk of synovial monocytes (MC) with synovial fibroblasts (SF) is a key step to the inflammatory process in rheumatoid arthritis (RA). Objectives: Herein, we investigated whether delivery of specific miRs by MC-derived MPs affects RASF behaviour. Methods: Blood samples of healthy volunteers and RA patients were collected. MPs were obtained by differential centrifugation. CD14 + cells were isolated from PBMCs by using positive selection and the cells were stimulated with 50 ng/ml recombinant human M-CSF for 6 days. Scanning electron microscopy, nanosight trafficking analysis and flow cytometry (FACS) have been applied to characterize MPs from human CD14 + MCs and THP-1 cells. Total and smallRNA sequencing were performed on macrophages (n=4) and RASFs (n=4) as well as on macrophage-derived MPs (n=4). (Pre-)miR-223 expression and copy number was quantified in cells or tissues via TLDA, qPCR & in situ hybridisation with specific primers and probes. Targeted pathways were identified using prediction algorithms (TargetScanHuman6.2). Transfer of miR-223 from MCs to SFs was determined by fluorescence microscopy, direct cell co-culture and FACS, as well as transwell co-culture. RASF proliferation assays with FGF-2 as positive control, as well as THP-1 derived MPs, miR-223 mimic, miR-223 inhibitor, control mimic and inhibitor were carried out. Results: MPs from MCs & THP-1 cells are about 250nm in size (range 50–800nm). SmallRNA sequencing revealed high levels of miR-223 in macrophages as opposed to a lack of its expression in RASF. If co-cultured with MCs for 3d, RASF acquire miR-223 expression, but not pre-miR-223 to a significant extent (n=6, Ct values <30) confirming transfer of mature miR-223 between cells. Prediction algorithms identified FBXW7 as a candidate target for miR-223 in RASF. FBXW7 acts as an ubiquitin ligase targeting cyclin E. Co-culture of RASF with THP-1 derived MPs increased RASF proliferation to a similar extent as FGF-2 (n=8, p<0.01). Transfection of RASF with miR-223 inhibitor prior to stimulation with THP-1 MPs abrogates their proliferative effect (n=5, p<0.05). miR-223 transfection (25nM & 50nM) itself led to an increase of RASF proliferation after 72 and 96h (n=6–8, p<0.01 for all). Conclusions: miR-223 transport from MCs to SFs by MPs represents a novel intercellular mechanism that could stimulate SF proliferation during initiation or chronicity of synovial inflammation in RA. References: Laffont, B. et al. Blood (2013) Acknowledgement: We wish to thank Derek Baxter, Diane Vaughan, Margaret Mullin, Pawel Herzyk, Julie Galbraith, Russka Shumnalieva for their support and technical assistance. Disclosure of Interest: None declared